The Dynamical Analysis of Computer Viruses Model with Age Structure and Delay. (27th April 2021) - Cao, Hui; Wang, Si; Yan, Dongxue; Tan, Hongwu; Xu, Hemiao
Abstract : This paper deals with the dynamical behaviors for a computer viruses model with age structure, where the loss of the acquired immunity and delay are incorporated. Through some rigorous analyses, an explicit formula for the basic reproduction number of the model is calculated, and some results about stability and instability of equilibria for the model are established. These findings show that the age structure and delay can produce Hopf bifurcation for the computer viruses model. The numerical examples are executed to validate the theoretical results.